The algorithm for determining the remaining resource of motor oil - A. P. Serkov; S. V. Korneev (Вестник СибАДИ)
There is presented an algorithm of the method for determining the remaining resource of motor oil of automobile transport. Method for diagnosing motor oils is based on the technology of assessing diagnostic parameters of the system "engine - motor oil" using methods of drop test and subsequent digital processing of drop test’s chromatograms.